Analisa Kerusakan Motor Starter Pada Marine Engine 3306 Caterpillar - Abdul Halik; Hidayat Hidayat; Muhammad Taufik; Baso Cante; Arwin Arwin (MEDIA PERSPEKTIF : Journal of Technology, 2022)
The starter motor is one of the most important components in the electrical system. This study was conducted to determine the damage to the electrical system of a heavy equipment unit.  The object under investigation is the starter motor on the planetary type Caterpillar 3306 engine. The method used in this study is library research which consists of collecting data from the Service Information System (SIS), Operation Maintenance Manual (OMM), and various modules related to the object of study. field observation by carrying out disassembly of the object is continued with a visual inspection and ends with measurements that will be compared with standard data. The results of this study show that the measurement results for speed are obtained 5169 rpm with standard specifications 7643 (out spec), on solenoid winding components for pull in resistance 0.5 ohms with standard specifications 0.43-0.49 ohms (out spec), hold in resistance 0.6 ohms with standard specifications 1.37-1.77 ohms (out spec), the field winding components 0.1 ohms with standard specifications 0.1 ohms (in spec),  x- and y-axis armature components are 51.9 mm each with a standard specificity of 52.0 mm (in spec), Commutator (in spec)